Analisis Kesulitan Belajar Matematika dalam Menyelesaikan Soal HOTs (Higher Order Thinking Skill) pada Materi Bangun Datar Siswa Kelas IV MI Ma’arif Depokrejo - Kurnia An Najiah; Faisal Faisal; Agus Nur Soleh (Tarbi: Jurnal Ilmiah Mahasiswa, 2022)
The purposes of this research is to describe the difficulties in learning mathematicsexperienced by fourth grade students of Islamic Primary School of Ma’arif (MI Ma’arif)Depokrejo in solving HOTS (Higher Order Thinking Skill) questions on the two dimentionalfigures. This research is a qualitative research with a descriptive research design. The researchsubjects were the fourth grade teacher of Islamic Primary School of Ma’arif (MI Ma’arif)Depokrejo and the fourth grade students of Islamic Primary School of Ma’arif (MI Ma’arif)Depokrejo with a total of 30 students. The method used in this research is a qualitative methodwhich includes interviews, observation, and documentation. The data collected is in the form oflearning implementation data when working on math HOTS questions. The data analysis techniqueused is data analysis according to Miles & Huberman which includes three stages, namely datareduction, data presentation, and drawing conclusions. The results showed that students' learningdifficulties in solving HOTS-based math problems varied according to the level of understandingand accuracy of students. The difficulty lies in the steps of solving mathematical problems, namelythe difficulty of understanding the problem, the difficulty of composing mathematical sentences,the difficulty of applying the formula, the difficulty of the calculation process, and the lack ofaccuracy